Understanding the regulation of iron nutrition: can it contribute to improving iron toxicity tolerance in rice? - Onaga, Geoffrey; Dramé, Khady Nani; Ismail, Abdelbagi M. (Commonwealth Scientific and Industrial Research Organisation, 2016)
Iron nutrition in plants is highly regulated in order to supply amounts sufficient for optimal growth while preventing deleterious effects. In response to iron deficiency, plants induce either reduction-based or chelation-based mechanisms to enhance iron uptake from the soil. Major physiological traits and genes involved in these mechanisms have been fairly well described in model plants like Arabidopsis thaliana (L. Heynh.) and rice (Oryza sativa L.). However, for rice, iron toxicity presents a major challenge worldwide and causes yield reductions because rice is widely cultivated in flooded soils. Nonetheless, rice employs different mechanisms of adaptation to iron-toxicity, which range from avoidance to tissue tolerance. The physiological and molecular bases of such mechanisms have not been fully investigated and their use in breeding for iron-toxicity tolerance remains limited. Efforts to precisely characterise iron-toxicity control mechanisms may help speed-up the development of tolerant rice varieties. Considering how far the understanding of iron dynamics in the soil and plants has progressed, we consider it valuable to exploit such knowledge to improve rice tolerance to iron toxicity. Here we present the mechanisms that regulate iron uptake from the rhizosphere to the plant tissues together with the possible regulators involved. In addition, a genetic model for iron-toxicity tolerance in rice, which hypothesises possible modulation of key genes involved in iron nutrition and regulation is presented. The possibility of incorporating such relevant regulators in breeding is also discussed.